PENGARUH SUHU TERHADAP PERURAIAN KADAR ASETOSAL PADA TABLET GENERIK DAN PATEN SECARA SPEKTROFOTOMETRI UV - Iswandi Iswandi (LPPM Akafarma Sunan Giri Ponorogo, 2022)
Acetosal has many properties or broad therapeutic effects, including analgesic, antipyretic, non-steroidal anti-inflammatory, antifibrinolysis, inhibition of prostaglandin biosynthesis, pain relief, and cardiovascular disorders. The purpose of this study was to determine the effect of storage temperature on acetosal content and acetosal decomposition in generic and patent tablets. Acetosal tablets were stored at 250C, 500C and 750C, then weighed 50.0 mg and dissolved with 5.0 mL of ethanol and aquabidestilata to 100.0 mL, then diluted and read with the maximum wavelength. The results were calculated as percent acetosal content and percent decomposition and were analyzed using the Two Way Anova statistical test. The levels of generic acetosal tablets at 250C, 500C and 750C respectively yielded 94.3% (± 0.64) ; 91.53% (±1.19) ; 81.43% (± 0.73). Acetosal levels in patent tablets at temperatures of 250C, 500C and 750C respectively yielded 96.06% (± 0.68) ; 92.74% (±0.53) ; 87.15% (± 0.67). Acetosal decomposition results in generic tablets at temperatures of 250C, 500C and 750C respectively yielded 5.07% (± 0.64) ; 8.47 %(± 1.19); 18.57% (± 0.73). The levels of acetosal decomposition products in patent tablets at temperatures of 250C, 500C and 750C respectively yielded 3.94% (± 0.68) ; 7,26 %(± 0,53) ; 12.85% (± 0.67). The results of the two-way ANOVA showed that there was a significant difference in the levels of acetosal and decomposition products between generic tablets and patented tablets which were affected by storage temperature.